Political Communication in Britain
XVII, 296 p. 20 illus., 16 illus. in color.
Keywords: Against prior expectations the 2017 General Election proved to be particularly dramatic, repeatedly stunning commentators from its surprise calling right through to its frenetic conclusion. In seven weeks a hitherto dominant Prime Minister saw her once seemingly unassailable lead in the polls eroded as support for her previously beleaguered rival surged. The subsequent restoration of two-party dominance contributed to the return of a hung parliament with profound consequences for both Theresa May and Jeremy Corbyn. Political Communication in Britain, the tenth volume in a series that began nearly four decades ago, revisits a momentous election by providing unique insights from the vantage point of those who fought, reported and researched a campaign that is likely to live long in the public imagination. Dominic Wring is Professor of Political Communication at Loughborough University, UK. Roger Mortimore is Professor ofPublic Opinion and Political Analysis at King’s College London, UK, and Director of Political Analysis at Ipsos MORI. Simon Atkinson is Chief Knowledge Officer at Ipsos MORI, UK.